2007
DOI: 10.1021/jf062584f
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Induction of Hydroxyl Radical Formation via 12-Lipoxygenase in Human Platelets:  An ESR Study

Abstract: The pro-oxidant activities of baicalein, morin, myricetin, quercetin, and rutin were examined in various cell-containing systems including human platelets, rat vascular smooth muscle cells, human umbilical vein endothelial cells (HUVECs), human THP-1 cells, and fibroblast cells. Electron spin resonance (ESR) results showed that only baicalein generated hydroxyl radicals in a resting human platelet suspension, whereas the other flavonoids showed no effects on any of the resting cell systems. A low concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Vanillin[ Fig.1(B)] is also one of main phenolic ingredients in Gastrodiaelata BL, which can be extracted from vanilla beans and possesses a popular odor for the utilization in perfume, food and medicine [22,23] . The pharmacological investigation [24] has proved that vanilla is of excellent biological activity, and can even be used by the injection of an effective dose amount [25] . Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] .…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin[ Fig.1(B)] is also one of main phenolic ingredients in Gastrodiaelata BL, which can be extracted from vanilla beans and possesses a popular odor for the utilization in perfume, food and medicine [22,23] . The pharmacological investigation [24] has proved that vanilla is of excellent biological activity, and can even be used by the injection of an effective dose amount [25] . Vanillin suppresses metastatic potential of human cancer cells via PI3K inhibition, decreases angiogenesis in vivo [26] and exhibits antibacterial and antimicrobial activities [27,28] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, platelets have been frequently reported as a vulnerable target of xenobiotic-induced cytotoxicity and peroxidase action on xenobiotic compounds may contribute to platelet cytotoxicity. The authors' previous study (32) demonstrated that 12-LOX and PHS were involved in OH • formation induced by natural flavonoids in platelets and suggested a role for these peroxidase systems in the xenobiotic-compound activation. COX-2 has been recognized as a potent pro-inflammatory cytokine and has been implicated in platelet aggregation (33).…”
Section: Discussionmentioning
confidence: 99%
“…A Bruker EMX electron spin resonance spectroscopy (ESR) spectrometer was used to detect the ESR trapping and the experimental protocol was modified from the previous report [15]. DPPH radical was used to generate the excess free radical.…”
Section: Methodsmentioning
confidence: 99%